Police Barracks, Trinidad - (:unkn) unknown (Goodwille and Wilson Ltd., Trinidad, 2010)
External view of the St. Vincent Street side of the Police Barracks building, Port of Spain, Trinidad. There are several persons walking on the streets outside the building.
Colour: Black and White; Style: Landscape; Other: Unbordered, Divided
Keywords: Trinidad and Tobago; Postcards; Police stations--Trinidad and Tobago; Public buildings--Trinidad and Tobago; 1908; Men--Trinidad and Tobago; Women--Trinidad and Tobago; Clothing and dress--Trinidad and Tobago; Hats--Trinidad and Tobago; Streets--Trinidad and Tobago; Architecture--Trinidad and Tobago; Fences--Trinidad and Tobago; Cities and towns--Trinidad and Tobago--Port of Spain; Shrubs--Trinidad and Tobago